The Costs of Open and Closed Access: Using the Finnish Research Output as an Example - Antero Laitinen, Markku; Saarti, Jarmo; Ilva, Jyrki (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2016)
The Open Access movement in scientific publishing has been gathering momentum in the European Union and its member states, partly due to the policies of some of its main research funders. Already we have seen encouraging research results on the effects of openness on the dissemination of scientific outputs. As business models of Open Access publishing are still under development, the aim of our paper is to assess the statistical tools and data that the Finnish libraries currently have for comparing the costs associated with different modes of disseminating scientific publications. We will also analyse the potential costs associated with Open Access publishing models and compare them with the current cost structure of – mostly – paywalled (PW) access. The discussion will include a description of current Finnish Open Access policies and their funding models. The financial analysis will be based on the statistical data found in the national Research Library Statistics database and the Finnish National Research Publications database, Juuli. We will discuss the alternatives on how best to develop statistical tools to estimate the true costs of scientific publishing.